2011
DOI: 10.1007/s11934-011-0208-y
|View full text |Cite
|
Sign up to set email alerts
|

Does Estrogen Have Any Real Effect on Voiding Dysfunction in Women?

Abstract: For many years, estrogen has been used to treat lower urinary tract dysfunction in postmenopausal women. The data supporting this practice vary. Large multi-institutional studies have shown little role for systemic estrogens in the treatment of urinary incontinence. Vaginal estrogen preparations show superiority to systemic estrogens for the treatment of irritative voiding symptoms in meta-analysis, but there is significant study heterogeneity and the practice remains debatable. Data from randomized controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…There has been conflicting evidence for the use of oral estrogen therapy to improve symptoms of OAB, as much of the data comes from observational studies. 38 Cardozo et al 39 found both subjective and urodynamic improvement in OAB symptoms in women taking estrogen compared with placebo; however, this was not statistically significant. Benness et al 40 found a statistically significant improvement in urgency in women taking vaginal estrogen compared with placebo.…”
Section: Detrusor Overactivitymentioning
confidence: 96%
“…There has been conflicting evidence for the use of oral estrogen therapy to improve symptoms of OAB, as much of the data comes from observational studies. 38 Cardozo et al 39 found both subjective and urodynamic improvement in OAB symptoms in women taking estrogen compared with placebo; however, this was not statistically significant. Benness et al 40 found a statistically significant improvement in urgency in women taking vaginal estrogen compared with placebo.…”
Section: Detrusor Overactivitymentioning
confidence: 96%
“…The predominant estrogen in human circulation is 17β-estradiol, a potent hormone known to regulate urinary bladder function [ 3 , 4 , 6 , 7 ]. 17β-Estradiol-induced UBSM relaxation has long been established in vitro [ 8 10 ] and in vivo [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Randomised-controlled trials confirm that oestrogen use in post-menopausal women decreases the rate recurrent urinary tract infections and urinary incontinence. 77 …”
Section: Urinary Tract Infection and Incontinencementioning
confidence: 99%